Fiber-optic communication systems - Agrawal, Govind P. ([S.l.] : Wiley-Interscience, 2002)
The Institute of Optics, University of Rochester * ".readers searching for a wide ranging and up-date view of fibre optic communication systems would do well to purchase this book."-International Journal of Electrical Engineering Education (on the Second Edition) * This comprehensive, up-to-date account of fiber-optic communication focuses on the physics and technology behind fiber-optic communication systems while covering both the systems and components aspects * Provides extensive details on the WDM technology and system design issues that have developed since the last edition * An Instructor's Manual presenting detailed solutions to all the problems in the book is available from the Wiley editorial department.